Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1289/ehp.01109s15
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species and interassay comparisons of phytoestrogen action.

Abstract: This paper compiles animal and human data on the biologic effects and exposure levels of phytoestrogens in order to identify areas of research in which direct species comparisons can be made. In vitro and in vivo assays of phytoestrogen action and potency are reviewed and compared to actions, dose-response relationships, and estimates of exposure in human subjects. Binding studies show that the isoflavonoid phytoestrogens are high-affinity ligands for estrogen receptors (ERs), especially ER beta, but have lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
1
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(119 citation statements)
references
References 210 publications
(163 reference statements)
3
105
1
7
Order By: Relevance
“…For matairesinol and equol, nondetectable concentrations were obtained for most of the serum samples. Detectable levels of equol in serum have been reported in previous studies, but the reported values were below our method's limit of detection (Adlercreutz et al, 1993;Whitten and Patisaul, 2001). Time of collection of the blood sample is an important variable for the determination of phytoestrogens because of their short halflives (King and Bursill, 1998).…”
Section: Discussioncontrasting
confidence: 60%
“…For matairesinol and equol, nondetectable concentrations were obtained for most of the serum samples. Detectable levels of equol in serum have been reported in previous studies, but the reported values were below our method's limit of detection (Adlercreutz et al, 1993;Whitten and Patisaul, 2001). Time of collection of the blood sample is an important variable for the determination of phytoestrogens because of their short halflives (King and Bursill, 1998).…”
Section: Discussioncontrasting
confidence: 60%
“…Their function is estrogen-like, but in contrast to the natural ligand estradiol they act in an organ selective and gene specific way . The estrogenic effects of specific phytoestrogens have been characterized to different degrees (Whitten and Patisaul, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…However, estrogenicity of genistein is only 1͞1,000th to 1͞10,000th that of E 2 (7). In addition, only a small fraction of circulating genistein or daidzein is the active aglycone.…”
mentioning
confidence: 99%
“…Work on estrogenic effects of phytoestrogens has focused on reproductive organs (7). However, thymus expresses both estrogen receptor (ER) ␣ and ER␤, and estrogen treatment of developing rodents induces thymic atrophy and immune suppression (8,9).…”
mentioning
confidence: 99%